Respuesta agronómica del haba (Vicia faba) y fréjol cuarentón (Phaseolus vulgaris) en asociación con cacao en el Centro Experimental Sacha Wiwa parroquia Guasaganda. - Bravo Bravo, Diana Carolina (2024)
The research was carried out at the “Sacha Wiwa” Experimental Center, with the main objective of evaluating the agronomic response of bean (Vicia faba) and forties bean (Phaseolus vulgaris) in association with cocoa. The project was financed by FIASA (Research Fund for Agrobiodiversity, Seeds and Sustainable Agriculture) was associated with this approach, seeking to promote research in the agriculture and livestock industry through the execution of plans, programs, and projects in agrobiodiversity, phylogenetic improvement, seed production, sustainable agriculture, technology transfer and innovation in the national agriculture and livestock sector. A Randomized Complete Block Design (RCBD) was established with four treatments and twelve replications with fourteen experimental units. Key agronomic variables were evaluated, such as days of emergence, percentage of emergence, plant height, days of flowering, days of pod formation, number of pods, weight of pods per treatment, and total weight. For this reason, periodic measurements were made and statistical techniques were used in treatments T2 and T3 in the mentioned variables implying a clear benefit in terms of agronomic performance with the combination of forties bean with cocoa 800 and bean with cocoa CCN-51 has proven to be especially effective in the development of vigorous growth and abundant production, where this performance was outstanding.